2015
DOI: 10.1016/j.cej.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of microcystin-LR and cylindrospermopsin by heterogeneous photocatalysis using a tubular photoreactor packed with different TiO2 coated supports

Abstract: The photocatalytic degradation of cyanotoxins in aqueous solutions using slurry suspensions of TiO2 implies a post-filtration step to retain the photocatalyst. In this work, 2D and 3D TiO2 thin films sup-ported in inert surfaces was proposed for the solar photocatalytic removal of cyanotoxins microcystin-LR (MC-LR) or cylindrospermopsin (CYN) in distilled and natural water under neutral pH conditions. The photocatalytic experiments were performed in a lab-scale tubular photoreactor with a compound parabolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…For photochemical applications, the reactor must be made of transparent material, and care should be taken to minimize the pressure drop over the bed. Whereas packed-beds or similar have been employed in wastewater treatment [45,46], few synthetic photochemical applications have appeared. Interesting examples are the synthesis of artemisinin from DHAA with supercritical CO 2 and O 2 feeds using a packed-bed of a porphyrin catalyst, reported by George, Poliakoff, and Rossen [47], and the TiO 2 -catalyzed synthesis of disulfides under aerobic conditions, reported by Noë l [48].…”
Section: Trends In Chemistrymentioning
confidence: 99%
“…For photochemical applications, the reactor must be made of transparent material, and care should be taken to minimize the pressure drop over the bed. Whereas packed-beds or similar have been employed in wastewater treatment [45,46], few synthetic photochemical applications have appeared. Interesting examples are the synthesis of artemisinin from DHAA with supercritical CO 2 and O 2 feeds using a packed-bed of a porphyrin catalyst, reported by George, Poliakoff, and Rossen [47], and the TiO 2 -catalyzed synthesis of disulfides under aerobic conditions, reported by Noë l [48].…”
Section: Trends In Chemistrymentioning
confidence: 99%
“…Microcystins are stable, water-soluble molecules and are rapidly absorbed by the liver resulting in harmful results such as cell necrosis, haemorrhage and death [189]. In recent years, significant attention has been given to the ever rising problem of these cyanotoxins occurring in aquatic sources, especially those that serve as sources of drinking water supply [189][190][191][192][193][194][195][196][197][198][199][200][201]. Choi et al [202] in 2007 reported that when using a visible light active (VLA) N-TiO 2 material under acidic conditions (pH 3.5), the adsorption and photocatalytic degradation of MC-LR is greatly improved.…”
Section: R Fagan Et Al / Materials Science In Semiconductor Processingmentioning
confidence: 99%
“…In addition, the high photoactivity of TiO 2 and metal-doped TiO 2 nanocatalysts supported over monolith channels for dyes photoreduction is obviously due to large illuminated surface area in monolith channels (Pinho et al, 2015), fast electron transfer with hindered recombination rates (Tahir et al, 2015a), high mobility of electron on the catalyst surface, efficient desorption of products and high photonic efficiency (Tahir et al, 2015b).…”
Section: Synthetic Dyesmentioning
confidence: 99%